Green Employee Involvement and Non-Financial Corporate Performance of Deposit Money Banks in South-West, Nigeria - Eniola, Sule Olatuni; Adekemi, Alagah, Drusilia; EO, Oshi, Joseph (International Journal of Business Management and Finance Research, 2022)
This study is to access the effect of one of the green human resource management practices (green employee involvement) on few non-financial performances of deposit money banks in South-West, Nigeria. The study examined the relationship between green employee involvement and non-financial corporate performance of deposit money banks in South-West, Nigeria. The actual problem that necessitated the research is to see if green employee involvement could be used in solving some of the unethical behaviours and attitudes in our deposit money banks especially in South-West, Nigeria. Survey design was used. The study population was the managerial staff of deposit money banks in the South-West of Nigeria with 330 as the sample size depending on Krejcie and Morgan sample determining table. Simple random sampling technique was applied to administer the research instrument. Structural Equation Modelling - AMOS was used in testing the three (3) hypotheses. The findings revealed that there is relationship between green employee involvement and non-financial corporate performance and that green employee involvement positively aid the non-financial performance of deposit money banks in South-West, Nigeria. Hence, the study recommended that organisations willing to increase their operational efficiency and innovation should embrace green employee involvement.